Coming up for air ebook - Kenneally, Miranda (Hundred Oaks, 2017)
Swim. Eat. Shower. School. Snack. Swim. Swim. Swim. Dinner. Homework. Bed. Repeat. All of Maggie's focus and free time is spent swimming. She's not only striving to earn scholarships—she's training to qualify for the Olympics. It helps that her best friend, Levi, is also on the team, and cheers her on. But Levi's already earned an Olympic tryout, so Maggie feels even more pressure to succeed. And it's not until Maggie's away on a college visit that she realizes how much of the "typical" high school experience she's missed by being in the pool. No one to shy away from a challenge, Maggie decides to squeeze the most out of her senior year. First up? Making out with a guy. And Levi could be the perfect candidate. After all, they already spend a lot of time together. But as Maggie slowly starts to uncover new feelings for Levi, how much is she willing to sacrifice in the water to win at love?